Future culinary students' career: do internship program experiences make a difference?/ Mas Affandy Mashuri, Mohd Onn Rashdi Abd Patah and Azdel Abdul Aziz - Mashuri, Mas Affandy; Abd Patah, Mohd Onn Rashdi; Abdul Aziz, Azdel (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2020)
Culinary Arts is one of the hospitality related programs offered in university, training institution and colleges. However, despite the increasing number of programs offered, the industry still faces issues of retaining culinary talents in the hotel industry. Therefore, the main purpose of this research is to investigate the relationship between internship program experience, overall satisfaction, and future career of culinary graduates. A total of three hundred (300) culinary program students from three Higher Education Institutions (HEIs) in Selangor, Malaysia was invited to participate. A total of 275 questionnaires were returned and analysed. Multiple regression was performed to assess the relationship between the study variables. Results showed that Appreciation and Feedback dimension had significant influences on future career. However, other sub-dimensions; Orientation and Supervisor Support, Work Atmosphere, Coordination between Institution and Organization and Exciting and Challenging work were not proven to be significant to future career. Findings also reported that all the dimensions of internship program experience to have significant impact with their overall satisfaction. These findings present significant information for HEI and the hotel industry on the importance of internship program to prepare students for the actual work setting in the future.